The Effect of Students’ Vocabulary Mastery through Dictation Games : English - Mislawiyadi Mislawiyadi; M. Faidlul Anwar Karim (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Game was an activity or form of entertainment that involved players in specific rules with the aim of creating a fun or challenging experience. Many students experienced difficulty in mastering English vocabulary, and for this reason, The purpose of this study was to use the dictation games method for assisting students in learning vocabulary in English. The research design employed was a quasi-experimental method, conducted at SMPN 1 Asembagus. The sample method employed was basic random sampling, and there were a total of 74 respondents divided into 37 respondents for the control group and 37 respondents for the experimental group. Subsequently, data processing and data analysis were conducted using a quantitative method. This research employed a questionnaire as the instrument for the pre- and post-tests. According to the study's findings, student's understanding of English vocabulary can be significantly impacted by the dictation games approach. The average score from the pre- and post-tests shows this. Pre-test mean score is 68.11; post-test mean score is 92.70. The result of the hypothesis test with the paired sample t-test is a t-score (+) 21.170 since the t-score > 1.729. The fact that the alternative hypothesis, or H1, is accepted and the null hypothesis, or H0, is rejected, it can be said that dictation game gives a positive effect on students’ vocabulary mastery.